NEW PARADIGMS IN EDUCATION AND TECHNOLOGIES: TRANSFORMING TEACHING AND LEARNING (International Seven Journal of Multidisciplinary, 2025)
The central theme of the research was to bring to reflection some contributions of theoretical-scientific knowledge about the possibilities inherent in the use of technologies in the classroom in the search for promoting meaningful learning. Thus, the main objective of the work was to investigate, through bibliographic review and qualitative descriptive approach, aspects considered relevant about the proposed theme, emphasizing the educational field today, using a multidisciplinary perspective. Thus, the study sought to show how learning can be enhanced through the use of digital technologies in the school environment. It is also worth noting that notes were raised in order to analyze the challenges and possibilities of the adoption of technologies by the teacher.